Mitochondrial gene expression is required for platelet function and blood clotting - Richman, T.R.; Ermer, J.A.; Baker, J.; Siira, S.J.; Kile, B.T.; Linden, M.D.; Rackham, Oliver; Filipovska, A. (2023)
Platelets are anucleate blood cells that contain mitochondria and regulate blood clotting in response to injury. Mitochondria contain their own gene expression machinery that relies on nuclear-encoded factors for the biogenesis of the oxidative phosphorylation system to produce energy required for thrombosis. The autonomy of the mitochondrial gene expression machinery from the nucleus is unclear, and platelets provide a valuable model to understand its importance in anucleate cells. Here, we conditionally delete Elac2, Ptcd1, or Mtif3 in platelets, which are essential for mitochondrial gene expression at the level of RNA processing, stability, or translation, respectively. Loss of ELAC2, PTCD1, or MTIF3 leads to increased megakaryocyte ploidy, elevated circulating levels of reticulated platelets, thrombocytopenia, and consequent extended bleeding time. Impaired mitochondrial gene expression reduces agonist-induced platelet activation. Transcriptomic and proteomic analyses show that mitochondrial gene expression is required for fibrinolysis, hemostasis, and blood coagulation in response to injury.